A Data-sharing Model Based on Blockchain for Power Grid Big Data. Issue 1 (February 2021) - Zhang, Xudong; Zhao, Linlin; Gao, Xiaoxin; Zhang, Xu
Abstract: In the existing smart grid, wireless sensor networks are widely deployed to monitor the entire grid's status to ensure the safe, reliable, and efficient operation of the grid. However, due to the storage mode of the infinite sensor network perception data based on the trusted central node in the smart grid, the smart grid exists information security issues such as the central node's vulnerability to malicious attacks and deliberate data tampering. In response to these information security issues, this paper proposes a data-sharing model based on blockchain technology and digital digest matching algorithm, which has the characteristics of decentralization, security and credibility, non-tampering, and protection of private data. The model uses the consortium blockchain technology to build a smart grid Data Storage Consortium Blockchain (DSCB). The data capability is taken as a unique token through the method of data capability to control the data access to achieve fine-grained access control with a resource as the unit. The capability update is convenient, and the capability withdrawal is supported to ensure the data security sharing between sensor nodes. Security analysis shows that the model can realize safe, effective, and privacy-protected data storage and sharing.